Trend in Incidence of Cervical Cancer in a National Tertiary Cancer Hospital of Nepal, 2012-2017 - Mulmi, Rashmi; Shrestha, Gambhir; Pathak, Ayodhya; Sharma, Manju; Dawadi, Tara; Siwakoti, Bhola (Nepalese Journal of Cancer, 2019)
Introduction: Cervical cancer is the first common cancer and a leading cause of mortality among Nepalese women. The trend of cervical cancer can be useful for effective planning and policymaking to reduce the burden of the disease. This study aims to determine the incidence of cervical cancer and assess its trend in over 6 years in a national tertiary cancer hospital.Methods: This was a descriptive study with secondary data analysis of new cervical cancer that were registered from 2012 to 2017 in the registry of B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal. Descriptive statistics along with the trend of cervical cancer were analyzed.Results: A total of 3,254 cervical cancer cases were registered during 2012 to 2017. It contributed to 11.7% of total cancer and 21.2% of total female cancer cases. The trend of cervical cancer was relatively constant with highest of 605 cases in the year 2016 and lowest of 459 in the year 2014. The most common age group was 45-59 years (44.6%) followed by 60-74 years (29.4%) and 30- 44 years (21.1%).Conclusions: The trend of cervical cancer is relatively constant over the study period. Organized awareness activities, HPV vaccination, and screening programs are recommended to prevent and control the burden of cervical cancer in the country.